2011
DOI: 10.1074/jbc.m110.197111
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric Gi Proteins Link Hedgehog Signaling to Activation of Rho Small GTPases to Promote Fibroblast Migration

Abstract: Evidence supporting the functionality of Smoothened (SMO), an essential transducer in most pathways engaged by Hedgehog (Hh), as a Gi-coupled receptor contrasts with the lack of an apparently consistent requirement for Gi in Hh signal transduction. In the present study, we sought to evaluate the role of SMO-Gi coupling in fibroblast migration induced by Sonic Hedgehog (Shh). Our results demonstrate an absolute requirement for Gi in Shh-induced fibroblast migration. We found that Shh acutely stimulates the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(175 citation statements)
references
References 41 publications
10
165
0
Order By: Relevance
“…21,23,[28][29][30] We demonstrated that recombinant Shh is capable of inducing a fast (15-minute) Akt phosphorylation in SMCs. We showed that Shhinduced Akt phosphorylation is entirely inhibited by the pan PI3K inhibitor Wortmannin, the PI3Kg selective inhibitor AS-252424 ( Figure 3A), and competition with the inactive mutant of PI3Kg 25 (supplemental Figure 7A), demonstrating that Shh-induced Akt phosphorylation is mediated via PI3Kg.…”
Section: Shh-dependent Activation Of Pi3kg and Erk1/2 Participates Inmentioning
confidence: 73%
See 1 more Smart Citation
“…21,23,[28][29][30] We demonstrated that recombinant Shh is capable of inducing a fast (15-minute) Akt phosphorylation in SMCs. We showed that Shhinduced Akt phosphorylation is entirely inhibited by the pan PI3K inhibitor Wortmannin, the PI3Kg selective inhibitor AS-252424 ( Figure 3A), and competition with the inactive mutant of PI3Kg 25 (supplemental Figure 7A), demonstrating that Shh-induced Akt phosphorylation is mediated via PI3Kg.…”
Section: Shh-dependent Activation Of Pi3kg and Erk1/2 Participates Inmentioning
confidence: 73%
“…At the cellular level, recombinant Shh was shown to induce SMC and pericyte proliferation and survival [16][17][18][19] and to contribute to PDGF-BB-induced myofibroblast proliferation. 20 Even though Shh was shown to induce the migration of various cell types such as fibroblasts, 21 ECs, 22 endothelial progenitors, 23 and monocytes, 24 its role and mechanism in SMC migration in vitro and in MC recruitment in vivo have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In cell culture studies, Shh has been shown to be required for cell motility by activating Rho GTPases through a ''noncanonical'' or Gli-independent pathway (Renault et al 2010;Sasaki et al 2010;Polizio et al 2011). In these scenarios, signaling activation is relayed from Smo to the G proteins or Tiam1, a GEF for Rac1 (Sasaki et al 2010;Polizio et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Shh-mediated Smo-dependent signaling has been implicated in MEF chemotaxis (43) and scratch healing (44), but the surface receptors are also not defined. In both cases, PTX-sensitive Gαi proteins (Gαi 1-3) have been implicated.…”
Section: Gas1-smo-gnaz Defines a Signaling Pathway For Shh-directed Ementioning
confidence: 99%